A comprehensive review on recent advances in the use of ethnomedicinal plants and their metabolites in snake bite treatment - Kumar, Ashish; Banjara, Rameshwari A.; Aneshwari, Roman Kumar; Khan, Junaid; Bernarde, Paulo Sergio (Frontiers in Pharmacology, 2025)
Snakebites are a severe medical and social issue, particularly in tropical and subtropical countries with minimal medical facilities, where the most dangerous snakes are found. Worldwide, most rural areas use medicinal plants alone or in combination as antidotes for snakebite treatment. Local knowledge of medicinal plants for snakebite treatment plays a more critical role in primary healthcare services in rural areas. As a result of this review, it is revealed that 39% of herbs, 38% of shrubs, 18% of trees, 2% of climbers, 2% of bulbs, and 1% of ferns have snake antivenom potential, which is indicative of the presence of numerous phytochemicals such as alkaloids, coumarins, curcuminoids, flavonoids, steroids, triterpenoids, and cinnamic acid in particular plants. According to the availability of information, the data focus on the plants, their families, and their parts from various literature sources. In the future, the valuable plants reported here and their phytoconstituents may be potential sources for developing effective natural drugs for snake bite treatments. Therefore, this review is a comprehensive study of the snake antivenom potential of various medicinal plants and their bioactive compounds.